Building the city: Everyday lives fo migrant workers - Jayne, Mark; Siying, Wu; Chenhui, Wu (London Routledge, 2026)
The book offers complementary blending of longstanding political-economic accounts of migration, gender, labour, and urban life alongside advances in feminist, postcolonial, post-structural, materialist, and more-than-representational theories. Drawing on these critical resources the authors explore the complexities of migrant$1 (Bs everyday past, present, and future lives.s